Search for top squarks in final states with one isolated lepton, jets, and missing transverse momentum in √s = 13 TeV pp collisions with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physical review, 2016)
The results of a search for the top squark, the supersymmetric partner of the top quark, in final states with one isolated electron or muon, jets, and missing transverse momentum are reported. The search uses the 2015 LHC pp collision data at a center-of-mass energy of √s=13  TeV recorded by the ATLAS detector and corresponding to an integrated luminosity of 3.2  fb−1. The analysis targets two types of signal models: gluino-mediated pair production of top squarks with a nearly mass-degenerate top squark and neutralino and direct pair production of top squarks, decaying to the top quark and the lightest neutralino. The experimental signature in both signal scenarios is similar to that of a top quark pair produced in association with large missing transverse momentum. No significant excess over the Standard Model background prediction is observed, and exclusion limits on gluino and top squark masses are set at 95% confidence level. The results extend the LHC run-1 exclusion limit on the gluino mass up to 1460 GeV in the gluino-mediated scenario in the high gluino and low top squark mass region and add an excluded top squark mass region from 745 to 780 GeV for the direct top squark model with a massless lightest neutralino. The results are also reinterpreted to set exclusion limits in a model of vectorlike top quarks.
Im steht der Buchstabe s unter dem Wurzelsymbol
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2827 weitere Personen]
Gesehen am 15.05.2020